2016
DOI: 10.5152/tjar.2016.05902
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture as an Antiemetic in Children who Underwent Adenoidectomy and/or Tonsillectomy

Abstract: Amaç: Postoperatif kusma genel anestezi sonrasında en sık karşıla-şılan problemlerden biridir. Etiyolojide pek çok faktörün tek başı-na veya birlikte etkili olduğu bilinmektedir. Akupunktur, Dünya Sağlık Örgütünün tamamlayıcı tedavi metodu olarak kabul ettiği bir medikal tekniktir. Burada çocuk hastalarda adenoidektomi ve/ veya tonsillektomi sonrasında görülen kusmanın tedavisi amacıyla Akupunktur deneyimimiz sunulmaktadır.Yöntemler: Çalışmaya genel anestezi altında adenoidektomi ve/ veya tonsillektomi uygulan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In the pediatric population, acupuncture, electroacupuncture, and laser acupuncture at the P-6 acupoint have all been used to prevent POV after tonsillectomy and/or adenoidectomy, hernia repair, circumcision, orchidopexy, chemotherapy, and strabismus procedures 321, [350][351][352][353][354][355][356][357][358][359][360][361][362] . However, there are other studies that used these modalities in both adults and children with negative results [363][364][365][366] .…”
Section: Nonpharmacologic Therapies For Ponv and Pdnvmentioning
confidence: 99%
“…In the pediatric population, acupuncture, electroacupuncture, and laser acupuncture at the P-6 acupoint have all been used to prevent POV after tonsillectomy and/or adenoidectomy, hernia repair, circumcision, orchidopexy, chemotherapy, and strabismus procedures 321, [350][351][352][353][354][355][356][357][358][359][360][361][362] . However, there are other studies that used these modalities in both adults and children with negative results [363][364][365][366] .…”
Section: Nonpharmacologic Therapies For Ponv and Pdnvmentioning
confidence: 99%
“…Similarly, Özmert et al found that acupuncture at P6 acupoint for at least 20 minutes has been associated with a lower incidence of PONV. 33 …”
Section: Discussionmentioning
confidence: 99%
“…6,9 In previous studies, acupuncture or EA produced relief of nausea symptoms. 4,5,7 For example, Dundee et al, in a series of studies with more than 500 female patients, found a significant reduction in PONV only by stimulating PC 6. 4 The lack of antinausea effect of EA in the present study, which is effective for the treatment of nausea of other causes, such as chemotherapy-induced and postoperative nausea, might indicate that there are different pathophysiology mechanisms in the development of nausea in motion sickness.…”
Section: Discussionmentioning
confidence: 99%
“…Electroacupuncture (EA) entails the application of an electric current to the fitted needles by means of a special device. Previous studies have shown benefits from the application of acupuncture and EA for prevention of and therapy for nausea from other causes, such as chemotherapyinduced nausea, 3,4 postoperative nausea, [5][6][7] and pregnancyrelated nausea in the first semester. 4,8 The present study was designed to research the effect of EA on the symptoms of motion sickness.…”
Section: Introductionmentioning
confidence: 99%